Prognostic Value of the Modified Glasgow Prognostic Score in Patients Undergoing Radical Surgery for Hepatocellular Carcinoma. Issue 36 (September 2015) - Ni, Xiao-Chun; Yi, Yong; Fu, Yi-Peng; He, Hong-Wei; Cai, Xiao-Yan; Wang, Jia-Xing; Zhou, Jian; Cheng, Yun-Feng; Jin, Jian-Jun; Fan, Jia; Qiu, Shuang-Jian; Yufang, Ma.
<x xml:space="preserve">Abstract</x> Abstract There is increasing and consistent evidence concerning the association of systemic inflammation and poor outcome in patients with hepatocellular carcinoma (HCC). The aim of this study was to identify a superior inflammation-based prognostic scoring system for patients with HCC undergoing hepatectomy. We analyzed two independent cohorts of a total of 723 patients with HCC who underwent radical surgery between 2010 and 2012. The prognostic value of the inflammation scores, including the Glasgow Prognostic Score (GPS), modified GPS (mGPS), neutrophil-to-lymphocyte ratio, platelet lymphocyte ratio, prognostic index, and prognostic nutritional index, as well as the Barcelona Clinic Liver Cancer and Cancer of the Liver Italian Program staging systems was analyzed in a test cohort of 367 patients and validated in a validation cohort of 356 patients. A high score with the mGPS was associated with large tumor size, vascular invasion, and advanced clinical stage. Multivariate analysis showed that the mGPS was independently associated with overall survival and disease-free survival, and had a higher area under the curve value in comparison with other inflammation-based scores. The results of this study demonstrated that the mGPS is an independent marker of poor prognosis in patients with resectable HCC and is superior to other inflammation-based scores.